Microbiological quality and portion analyses of doner sandwiches - (:unkn) unknown (DEUTSCHER FACHVERLAG GMBH, 2018)
In this study, 35 chicken and 40 beef doner sandwiches were collected from Istanbul, and microbiological quality of meat component and portion sizes of the samples were analyzed. Mean TAC (Total Aerobic Count) results obtained were 6.99 +/- 1.5 log and 6.80 +/- 1.7 log cfu/g for beef and chicken doner, respectively. Enterococcus was most frequently isolated from the beef (72.5%) and chicken (27%) doner with a mean of 3.26 +/- 0.87 log and 3.34 +/- 0.94 log cfu/g, respectively. Escherichia coli were isolated from 25% of beef (2.97 +/- 0.6 log) and 34.2% of chicken 12.98 +/- 0.6 log) doner samples. Out of 75 doner meat samples, Staphylococcus aureus was isolated from 21% (2.9 +/- 1.04 log), Bacillus cereus from 2.6% (1.8 +/- 0.14 log), and Clostridium perfringens from 2.6% (3.15 +/- 0.1 log) of samples. Listeria monocytogenes was isolated from one beef doner sample. No Campylobacter and Salmonella spp. were detected. The amount of meat and salad served was 38.7-122.6 g and 8.81-125.2 g, respectively. Excluding one sample contaminated with L. monocytogenes, the microbiological quality of the collected samples was generally within the satisfactory limits. However, taking into consideration the risk due to non-standardized heat treatment and unequal meat and salad portion sizes between different buffets, the quantity regulations for doner sandwiches remain necessary.
Keywords: KEBABS; IDENTIFICATION; SOLD